Telecommunications cost management - DiMarsico, Brian (Auerbach Publications, 2003)
Most telecom books focus on either traditional telecom billing audits or pure technology, with the cost saving ideas buried deep in the text. Busy decision-makers need the specifics quickly, without having to plow through details that do not affect the economics of a project. Telecommunications Cost Management takes cost saving techniques and brings them to the forefront where managers and decision makers can quickly use them for real world cost reductions or efficiency gains. Traditional bill auditing texts provide recommendations but only within the context of the existing architectu.
Includes index
Keywords: Telecommunication -- Cost control; Télécommunications; Coût; Contrôle